Exploring interpersonal communication strategies in the healthcare system: insights from Barangay health workers (BHW) in the Philippines - Camasin, Angelica; Estur, Ronette; Jomadiao , Cristine; Paet, Ashley Shan; Nacionales, Joseph; Claridad, Norberto (Yayasan Mitra Persada Nusantara, 2023)
Effective communication between providers and patients is one of the most important factors for achieving better health outcomes in the delivery of healthcare and in order to achieve effective communication, the use of the right communication strategy is beneficial. In relation to this, Barangay Health Workers (BHW) are exposed to a lot of interpersonal communication between them and their constituents. With the lack of studies on BHW, it is important to understand the nature of their work by exploring the interpersonal communication strategies they use and how it helps them resolve healthcare miscommunication in their areas. This qualitative research was guided by interpretative phenomenological analysis in analyzing the experiences of BHW in terms of communication. The data was gathered from 18 BHWs using semi structured interviews. Based on thematic analysis, the following are the interpersonal communication strategies employed by BHWs’: interaction in a face-to-face context, usage of a particular language as means of communication, use of non-verbal communication, informing in an appropriate manner, use of electronic devices to transmit information, and observance of ethical communication. The participants also shared the contribution of these strategies towards overcoming miscommunication: helps in relaying information effectively which leads to better understanding of constituents, helps reduce conflict between the BHW and the constituents, and helps encourage constituents and change their perceptions.